Impact of Prior Cancer on the Prognosis of Patients With Laryngeal Cancer: A Population-Based Study Using the Surveillance, Epidemiology, and End Results Database - Chen, Kailin; Tian, Lamei; Li, Yajun; Jin, Yi; Liu, Huai; Wang, Hui (Frontiers in Oncology, 2020)
BACKGROUND: Little is known about the clinical significance of laryngeal cancer as a subsequent malignancy. We aimed to determine the prevalence and prognostic impact of a prior cancer history among patients with laryngeal cancer. METHODS: We identified patients diagnosed with laryngeal cancer between 2004 and 2011 in the Surveillance, Epidemiology, and End Results (SEER) database. Variables were compared using the t-test and chi-squared test as appropriate. Matched 1:1 case-control adjusted Kaplan-Meier analyses and Cox regression models were performed to evaluate the impact of prior cancer on overall survival (OS). RESULTS: Among 2,0987 patients with laryngeal cancer, nearly one-fifth (n=3915,18.65%) had a prior cancer. The most common prior cancers were prostate (588, 28.1%), lung and bronchus (354, 16.9%), and head and neck (306, 14.6%). A total of 73.4% of the prior cancers were diagnosed within 5 years of the laryngeal cancer diagnosis. Compared to patients without prior cancer, a worse survival was significantly associated with a prior cancer among laryngeal cancer patients, regardless of the interval timing of the prior cancer (log-rank tests P<0.001). Furthermore, prior cancer was an independent predictor of worse OS based on the Cox regression model [hazard ratio (HR) =1.396, 95% confidence interval, 1.336 to 1.458]. In addition, patients with prior lung and bronchus cancer tended to have the worst survival (log-rank tests P<0.001) CONCLUSIONS: Prior cancer has an adverse effect on clinical outcomes among patients with laryngeal cancer. These results suggest that individualized treatment should be seriously considered in patients with laryngeal cancer and a history of prior cancer, regardless of the interval time of prior cancer.